2017
DOI: 10.1670/16-078
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Release, but Not Cool Winter Temperatures, Reduces Post-Translocation Dispersal of Jewelled Geckos

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…Restoring the natural ecological community on Mana Island, including barking geckos and other lizard species, is a key conservation goal for the island (Miskelly 1999). Following the previous failed hard-release translocation of barking geckos to Mana Island (Knox & Monks 2014) and research demonstrating the potential of penned release for green gecko translocations (Knox & Monks 2014;Knox et al 2017) the decision was made to attempt a penned release for barking geckos on Mana Island in 2018. A release pen was constructed by members of the Friends of Mana Island Trust based on best practice techniques for the translocation of green geckos, see Monks et al (2017) for details.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Restoring the natural ecological community on Mana Island, including barking geckos and other lizard species, is a key conservation goal for the island (Miskelly 1999). Following the previous failed hard-release translocation of barking geckos to Mana Island (Knox & Monks 2014) and research demonstrating the potential of penned release for green gecko translocations (Knox & Monks 2014;Knox et al 2017) the decision was made to attempt a penned release for barking geckos on Mana Island in 2018. A release pen was constructed by members of the Friends of Mana Island Trust based on best practice techniques for the translocation of green geckos, see Monks et al (2017) for details.…”
Section: Methodsmentioning
confidence: 99%
“…The penned release strategy (restricting dispersal for a pre-determined period of time to enable animals to habituate to the release area and form stable territories within the release site; Bright & Morris 1994) shows promise as a tool for increasing the success rate of herpetofaunal translocations (Germano & Bishop 2008), but has received little scientific attention. Studies on gopher tortoises (Gopherus polyphemus; Tuberville et al 2005) and jewelled geckos (Naultinus gemmeus; Knox & Monks 2014;Knox et al 2017) demonstrate that penned releases reduce initial dispersal and increase site fidelity, which may ultimately increase the probability of population establishment and growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a small handful of translocation efforts have applied soft release to lizard species. Knox and Monks [ 15 ] and Knox et al [ 18 ] showed that soft releasing Jewelled Geckos ( Naultinus gemmeus ) resulted in less dispersal behavior and smaller home ranges than hard released individuals. Fitzgerald et al [ 19 ] attributed the successful reintroduction of St. Croix Ground Lizards ( Ameiva polops ) to Buck Island at least partially to soft release.…”
Section: Introductionmentioning
confidence: 99%